2022
DOI: 10.3390/bioengineering9030112
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticles as a Component of Peptide-Based DNA Delivery System for Suicide Gene Therapy of Uterine Leiomyoma

Abstract: Suicidegene therapy is considered a promising approach for the treatment of uterine leiomyoma (UL), a benign tumor in women characterized by precise localization. In this study, we investigate the efficiency of αvβ3 integrin-targeted arginine-rich peptide carrier R6p-cRGD electrostatically bound to magnetic nanoparticles (MNPs) for targeted DNA delivery into the UL cells. The physico–chemical and cytotoxic properties, transfection efficiency, and specificity of R6p-cRGD/DNA/MNPs polyplexes were evaluated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Large aggregates of polyplexes have the potential to interact with cell membranes and, as a result, some of these complexes can be taken up by the cells. Similar findings were obtained in our previous study of peptide-based polyplexes combined with anionic magnetic nanoparticles [ 22 ]. Another important discovery emerged from the transfection studies.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Large aggregates of polyplexes have the potential to interact with cell membranes and, as a result, some of these complexes can be taken up by the cells. Similar findings were obtained in our previous study of peptide-based polyplexes combined with anionic magnetic nanoparticles [ 22 ]. Another important discovery emerged from the transfection studies.…”
Section: Resultssupporting
confidence: 91%
“…During intercellular interactions, phosphorylated ganciclovir is transferred to neighboring cells, and this phenomenon is closely linked to this process [ 16 ]. It is important to note that the suicide gene therapy that uses the HSV-TK/GCV system has already been employed in gene therapy research of uterine leiomyoma [ 7 , 10 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we developed several gene delivery systems based on matrix polymerized or polycondensed crosslinking peptides modified with iRGD or cycloRGD ligands [ 33 , 53 , 54 ]. Developed non-viral carriers were used for HSV-TK gene transfer to the cellular model of uterine leiomyoma and suicide gene therapy effects were accessed by different methods including an alamarBlue assay.…”
Section: Resultsmentioning
confidence: 99%
“…According to alamarBlue assay data the most pronounced therapeutic effect—elimination of 57% UL cells was registered for R6p-cRGD/pPTK1 polyplexes; however, the application of RGD-R6p-0,75/pPTK1 and RGD1-R6/pPTK polyplexes was not much less efficient—53% and 46%, respectively [ 33 , 53 ]. In addition, it should be noted that a combination of R6p-cRGD/pPTK1 polyplexes with magnetic nanoparticles decreased the therapeutic effect—only 33% of UL cells were eliminated; however, transfection time was greatly decreased [ 54 ]. Thus, it can be concluded that the application of reducible polycondensed R6p carrier has a major impact on the transfection efficacy and HSV1-TK-mediated therapeutic effect.…”
Section: Resultsmentioning
confidence: 99%
“…It reduces transfection time and improves delivery of pDNA encoding thymine kinase gene for the herpes simplex virus type I (HSV-1). Therefore, it shows a potential nonviral-based approach for the treatment of uterine leiomyoma …”
Section: Biomedical Applications Of Nanopeptidesmentioning
confidence: 99%